2006
DOI: 10.1002/ajh.20656
|View full text |Cite
|
Sign up to set email alerts
|

IAP family protein expression correlates with poor outcome of multiple myeloma patients in association with chemotherapy-induced overexpression of multidrug resistance genes

Abstract: Multidrug-resistant (MDR) multiple myeloma (MM) patients who fail chemotherapy frequently express MDR1 protein, which serves as an efflux pump that protects neoplastic cells. The expression of lung resistance protein (LRP), which mediates intercellular and nucleocytoplasmic transport, is also correlated with chemotherapy resistance and shorter survival of MM patients. Here, we investigated the chemotherapy-induced change of MDR expression in MM patients using quantitative RT-PCR. Overall expression levels of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 31 publications
(32 reference statements)
4
68
0
Order By: Relevance
“…Growing evidence has indicated that survivin expression plays an essential role in drug resistance (reviewed Li 3 ). Our data and Nakagawa's report 30 underline this finding in MM and raise the hypothesis that inhibiting survivin may improve MM treatment.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Growing evidence has indicated that survivin expression plays an essential role in drug resistance (reviewed Li 3 ). Our data and Nakagawa's report 30 underline this finding in MM and raise the hypothesis that inhibiting survivin may improve MM treatment.…”
Section: Discussionsupporting
confidence: 83%
“…In line with our results, a recent report indicates that the expression ratios for survivin were significantly higher in MM patients with poorer outcome, especially after chemotherapy. 30 Although a larger cohort of patients would be necessary to confirm our results (as soon as a reliable survivin mAb for flow cytometry analysis becomes available), our results strongly argue for survivin participation in myeloma progression. However, it would be of particular interest to study survivin involvement in the first steps of oncogenesis in MM.…”
Section: Discussionsupporting
confidence: 54%
“…Although the correlation between Pgp and survivin expression is still debated in drug resistance, the overexpression of Pgp together with the upregulation of survivin was determined in association with the poor prognosis of the patients. 25) In our report, the mRNA expression of survivin was significantly suppressed after the Pgp was inhibited by its specific inhibitor verapamil. Verapamil, a calcium channel blocker, inhibits the efflux function of Pgp and cytoskeletal transfer and therefore plays an important role in circumvention of native and acquired chemoresistance of cancer cells.…”
Section: Effect Of Survivin On Pgp Functionmentioning
confidence: 58%
“…Increased expression of the IAP family proteins, including XIAP and survivin, correlate with poor outcome and chemotherapy-induced drug resistance in MM (46). The mechanism by which XIAP and survivin are reduced by OSU-03012 remains uncertain, although it is known that Akt activates these prosurvival genes (47,48).…”
Section: Discussionmentioning
confidence: 99%